2014
DOI: 10.1515/ijamh-2012-0111
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with anorectal malformation: physical outcome, sexual health and quality of life

Abstract: Adolescents with ARM have considerable intestinal symptoms, which influence QoL and require adaption in intimate situations. A referral to adult care seems to be important, and continuous cooperation between the pediatric surgeon and adult care is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 15 publications
2
26
1
9
Order By: Relevance
“…The prevalence of severe incontinence did not differ between young and old age groups, both for women and men with ARM. 14 The frequency of constipation was significantly higher in women (62%) than men (35%). There was no difference in frequency between children with perineal fistula and other ARM subtype groups, both in women and men.…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of severe incontinence did not differ between young and old age groups, both for women and men with ARM. 14 The frequency of constipation was significantly higher in women (62%) than men (35%). There was no difference in frequency between children with perineal fistula and other ARM subtype groups, both in women and men.…”
Section: Discussionmentioning
confidence: 92%
“…No previous studies have reported on gas‐related problems in healthy children, but due to its importance for quality of life, the issue has been included in the regular follow‐up in the International Registry of children with anorectal malformations. Male adolescents with anorectal malformations have reported that they experienced gas‐related problems which influenced their quality of life . We therefore advocate that gas‐related issues should also be included in future studies regarding bowel function, as they probably play an important role in the daily life of children and adolescents and might be connected to constipation and the need for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Children born with congenital pelvic floor malformations are reported to have vulnerable bowel function (10)(11)(12)(13)(14). To determine adequate goals for their bowel management and treatment, it is important to compare their bowel function to that of healthy children.…”
Section: Introductionmentioning
confidence: 99%
“…Fecal incontinence is reported in almost 30-50 % of the adolescent patients after surgery [6]. The long term outcome relates with ARM sub types, age at presentation and associated anomalies [7].…”
Section: Discussionmentioning
confidence: 99%